(untitled) (ART AND CULTURE BULLETIN, 2023)
The article analyzes the developments related to the support of non-state media in Uzbekistan in the years of independence, in particular the emergence of regional radio and television in Karakalpakstan, the further expansion of the material and technical base and the opening of non-state television and radio channels. Basically, many thoughtful opinions are expressed about the emergence of radio channels «Nukus-FM», «Ellikkala’a TV», «Turtkul TV», «Jaslar TV», «Amudarya TV».